TOTAL NON-STRUCTURAL CARBOHYDRATE (TNC) OF THREE CULTIVARS OF NAPIER GRASS (Pennisetum purpureum) AT VEGETATIVE AND REPRODUCTIVE PHASE - Budiman; R. D. Soetrisno; S. P. S. Budhi; A. Indrianto (Journal of the Indonesian Tropical Animal Agriculture, 2011)
An experiment was conducted to determine Total Non-structural carbohydrates (TNC) of three cultivars of napier grass (Pennisetum purpureum) harvested at vegetative and reproductive phases. The cultivars tested were Taiwan (Gt), King (Gk) and Mott (Gm) and arranged in a 3 x 2 of treatments with four replicates following nested design. The results showed that the highest sugar content (P<0.01) was found in Gt cultivar and the lowest was in Gm cultivar. The highest starch content (P<0.01) was found in Gk cultivar and the lowest was in Gt cultivar. TNC content of Gt and Gk cultivars were not significantly different, but both were significantly higher (P<0.01) compared with the Gm cultivar. It can be concluded, that there were differences in TNC between cultivars, however, the TNC content in Gk cultivar was not different with Gt cultivar, while Gm cultivar have the lowest (P<0.01) TNC content. At reproductive phase all cultivars have higher (P<0.01) TNC and starch content than at vegetative phase.